ANALISIS RISIKO KECELAKAAN LALU LINTAS BERDASAR TIPE KEPRIBADIAN DAN PELANGGARAN PADA PENGENDARA SEPEDA MOTOR - Defia Rosalina Anwar (The Indonesian Journal of Public Health, 2017)
It is reasonable that the traffic accident increased because of the massive motor vehicle accident. WHO recorded that the traffic accident was the third most enormous killer after tuberculosis and coronary heart disease. The majority of motorcyclist is teenager that causes the increase of traffic accident. This research was conducted to acknowledge the relation between the type of personality and the violation of motorcyclist toward the traffic accident occurred to senior high school student. This research was analytical observation using two stage random sampling method. The population of the research was all student in Sampang regency in 2017. It was involving 127 respondents. The variables applied were the type of personality and the violation of motorcyclist (including traffic sign and road markings). The data was analysed by Chi Square and suggested that (α = 0.05) the type of personality (p = 0.537; RR 1.457), and the violation of the motorcyclist (p = 1; RR 0.930) have no significant relation to the traffic accident among senior high school student. The conclusion of this research is there is no relationship between p ersonality type, violation by motorcycle with the incident of traffic accident. It is suggested to  high school students not to drive a motor vehicle if they do not have a driver’s license, in order to minimize the occurrence of  traffic accidents.